Carbon nanotube cathodes covered on the cylindrical surface of a fiber. Issue 22 (11th March 2015) - Wei, Xianqi; Zhu, Youzhang; Xia, Xianjun; Wang, Xiaoli; Liu, Weihuan; Li, Xin
<x xml:space="preserve">Abstract</x> Carbon nanotube (CNT) arrays were synthesized on the cylindrical waveguide surface of a quartz optical fiber by chemical vapor deposition (CVD) to serve as field emission cathodes.